1978
DOI: 10.1055/s-0038-1646739
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Estimation of Coagulation Factors in Liver Disease. The Diagnostic and Prognostic Value of Factor XIII, Factor V and Plasminogen

Abstract: Summary20 coagulation parameters were investigated in 144 patients with different liver diseases. The groups of acute hepatitis, chronic active hepatitis and liver cirrhosis were compared and the prognostic value of the coagulation analyses investigated. It is clear that the determination of the factor V activity is a good and easy test for detection of actual liver function. Repeated controls over several weeks revealed with a statistical significance (p <0.0005) that all patients with a factor XIII below … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
5

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 8 publications
(8 reference statements)
2
22
0
5
Order By: Relevance
“…The results of this investigation agree with a previous report showing low Normotest, Prekk, AT III, plasminogen and a 2-antiplasmin values in patients with chronic liver dis ease [8,[12][13][14]. With regard to the relation ship between these blood coagulation param eters and HBF, our study only partially agrees with the investigation of Fujii et al [5] which showed a good correlation between HBF, Normotest, and serum albumin in pa tients with chronic liver disease.…”
Section: Discussionsupporting
confidence: 62%
“…The results of this investigation agree with a previous report showing low Normotest, Prekk, AT III, plasminogen and a 2-antiplasmin values in patients with chronic liver dis ease [8,[12][13][14]. With regard to the relation ship between these blood coagulation param eters and HBF, our study only partially agrees with the investigation of Fujii et al [5] which showed a good correlation between HBF, Normotest, and serum albumin in pa tients with chronic liver disease.…”
Section: Discussionsupporting
confidence: 62%
“…In fact, low plasma levels of these proteins have been reported in chronic liver disease and considered as a consequence of the impaired hepatic synthesis [2][3][4][5]. The evaluation of these proteins in chronic liver disease shows that plasma levels of ATIII, Prekk and plas minogen seem to be a good index of liver function [2,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of these proteins in chronic liver disease shows that plasma levels of ATIII, Prekk and plas minogen seem to be a good index of liver function [2,4,5]. But the impaired hepatic synthesis could not be the only mechanism involved in such a condition; chronic liver disease, in fact, can be complicated by hyper fibrinolysis or chronic disseminated intra vascular coagulopathy (cDIC) and these two conditions could affect per se the plasma lev els of these proteins [6,7], However, these two last possibilities have not been taken into account in previous research [2,4,5], apart from the investigation of Annan et al [3].…”
Section: Introductionmentioning
confidence: 99%
“…Severity o f liver cirrhosis is currently clas sified according to Child, as stages A , B and C , corresponding to mild, moderate and severe cirrhosis, respectively [1], and can be further divided into subclasses according to Pugh's modification [2,3], Several studies have investigated haemo stasis unbalance in these different stages, to assess both the diagnostic and the prognostic value o f coagulation parameters, in cirrhotic patients scored as Child A , B and C [4][5][6][7][8][9][10][11][12][13][14][15], Some reports indicate that coagulation inhibi tors are significantly reduced in liver cirrhosis in degrees roughly proportional to the impair ment o f liver synthesis function [16][17][18][19], However, in these studies the stage o f liver cirrhosis was not accurately defined (accord ing to Pugh score), nor were the correlation between levels o f protein C (PC) and its natu ral cofactor protein S (PS) investigated throughout the evolution o f the disease. The aim o f the present study was to evaluate the extent and the correlation in the change o f the main haemostatic parameters and, more spe cifically, o f the coagulation inhibitors P C , PS and antithrombin III (AT III), in the evolu tion o f the different stages o f liver cirrhosis scored according to Pugh's modifications of Child's classification.…”
Section: Introductionmentioning
confidence: 99%